Comparing Discounting of Potentially Real Rewards and Losses by Means of Functional Magnetic Resonance Imaging - Pinger, Mathieu; Thome, Janine; Halli, Patrick; Sommer, Wolfgang H.; Koppe, Georgia; Kirsch, Peter (Frontiers in Systems Neuroscience, 2022)
Aim: Delay discounting (DD) has often been investigated in the context of decision making whereby individuals attribute decreasing value to rewards in the distant future. Less is known about DD in the context of negative consequences. The aim of this pilot study was to identify commonalities and differences between reward and loss discounting on the behavioral as well as the neural level by means of computational modelling and functional Magnetic Resonance Imaging (fMRI). Neural differences between discounting of losses and rewards were furthermore compared to differences of loss and reward anticipation. Method: We conducted a study combining an intertemporal choice task for potentially real rewards and losses (decision-making) with a monetary incentive/loss delay task (reward/loss anticipation). Thirty healthy participants (age 18-35, 14 female) completed the study. In each trial, participants had to choose between a smaller immediate loss/win and a larger loss/win at a delay of two weeks. Task-related brain activation was measured with fMRI. Results: Hyperbolic discounting parameters of loss and reward conditions were correlated (r = .56). There was no difference between frequency of loss and reward discounting. During decision-making, BOLD activation was observed in the parietal and prefrontal cortex, with no differences between reward and loss conditions. During reward and loss anticipation, dissociable activation was observed in the striatum, the anterior insula and the anterior cingulate cortex. Conclusion: We observed DD in both the reward and loss condition, with evidence for similar behavioral and neural patterns in the two conditions. Intertemporal decision-making recruited the fronto-parietal network, while reward and loss anticipation were related to activation in the salience network. We summarize and discuss methodological issues and possible solutions for comparing neural correlates of aversion and reward.